Top-Down Proteoform Analysis by 2D MS with Quadrupolar Detection - Polák, Marek; Palasser, Michael; Kádek, Alan; Kavan, Daniel; Wootton, Christopher A; Delsuc, Marc-André; Breuker, Kathrin; Novák, Petr; van Agthoven, Maria A (Analytical chemistry, 2023)
Two-dimensional mass spectrometry (2D MS) is a multiplexed tandem mass spectrometry method that does not rely on ion isolation to correlate the precursor and fragment ions. On a Fourier transform ion cyclotron resonance mass spectrometer (FT-ICR MS), 2D MS instead uses the modulation of precursor ion radii inside the ICR cell before fragmentation and yields 2D mass spectra that show the fragmentation patterns of all the analytes. In this study, we perform 2D MS for the first time with quadrupolar detection in a dynamically harmonized ICR cell. We discuss the advantages of quadrupolar detection in 2D MS and how we adapted existing data processing techniques for accurate frequency-to-mass conversion. We apply 2D MS with quadrupolar detection to the top-down analysis of covalently labeled ubiquitin with ECD fragmentation, and we develop a workflow for label-free relative quantification of biomolecule isoforms in 2D MS.
Keywords: Fourierova analýza; cyklotrony; Proteomics; Cyclotrons; Fourier Analysis; tandemová hmotnostní spektrometrie; Tandem Mass Spectrometry; ubikvitin; proteomika; Ubiquitin